CREATING TOURISM SECTOR OPPORTUNITIES IN THE TIME OF THE COVID-19 PANDEMIC - Zulki Zulkifli Noor (Sosiohumaniora, 2022)
Indonesia began to experience the COVID-19 pandemic from March 2020, this caused the national economy to be disrupted, so that the welfare of the community declined, especially in the tourism sector which was most affected by the ban on people from leaving their homes, which is a policy of Large-Scale Social Restrictions on the Implementation of Community Activity Restrictions by the Government. The policy requires restrictions on social activities in various public places and reduces the mobility of people to travel. This article aims to build strategic steps in creating opportunities for the tourism sector to continue to make a meaningful contribution to the national economy and anticipate the challenges of the tourism sector during the COVID-19 pandemic. The research method with a qualitative approach is used in this study to examine the literature through various sources, such as news in the mass media, relevant previous research results, and government policies. From the results of the literature review, it is known that there are several things that can be done to create opportunities in the tourism sector in order to improve the nation’s economy, namely: providing fiscal stimulus to the tourism sector, strengthening Indonesia’s tourism nation branding, developing virtual tourism ideas, and implementing CHSE certification for tourism destinations.